PENGARUH BRAND IMAGE, REFERENCE GROUP DAN LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE PADA GENERASI Z DI SURABAYA - Agustina, Agustina; Estik Hari Prastiwi (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
This study aims to analyze and prove the influence of brand image, reference group, and Lifestyle partially and simultaneously on iPhone smartphone purchase decisions for generation Z in Surabaya. The study used a quantitative approach. The sampling technique in this study was performed using Nonprobability sampling and Purposive sampling is a sampling technique based on the characteristics of at least 17 years old., domiciled in East Surabaya and has used or is using an iPhone Smartphone with a sample of 100 respondents. Data tests used are instrument test, classical assumption test, t test and F test. Data analysis using linear regression multiple coefficiency determination (R2). The results of the research show that the brand image variable has a significant influence on the decision to purchase a generation Z iPhone smartphone in Surabaya, the reference group has a significant influence on the decision to purchase a generation Z iPhone smartphone in Surabaya, lifestyle has a significant influence on the decision to purchase a generation Z iPhone smartphone in Surabaya, and brand image, reference group, and lifestyle simultaneously have a significant influence on purchasing decisions for Generation Z iPhone smartphones in Surabaya.